A qualitative study exploring motivations for participating in research among women who use opioids - Bagley, Sarah M.; Maschke, Ariel D.; Harris, Miriam T. H.; Walley, Alexander Y.; Johnson, Samantha; Hurstak, Emily; Farley, John; Keller, Sarah G.; McMahan, Vanessa M.; Barrett, Cynthia; Coffin, Phillip O.; Gunn, Christine M. (PLOS ONE, 2025)
Objectives We assessed the acceptability of four recruitment strategies and explored facilitators and barriers to research engagement among women who use opioids. Methods We recruited self-identified women reporting past 14-day non-prescribed opioid use using four recruitment approaches: community outreach in collaboration with community-partners; snowball sampling; social media campaigns; and passive recruitment through distribution of print materials at community programs. We collected participant demographics, type of recruitment, and substance use via an interview-administered survey. Qualitative interviews explored women’s research experiences, and facilitators and barriers to research engagement. Analysis employed a combination of inductive and deductive approaches to identify themes relevant to women’s engagement in research. Results Of 36 enrolled participants, median age was 49 years, 16% were Black, 58% were white, 14% were Hispanic, and 58% had their own house or apartment. We recruited 12 women through community outreach, two through snowball sampling, three through social media, and 19 through print materials. Interviews identified four themes: (1) highest trust when recruited through community organizations and lowest trust when recruited through social media; (2) desire to improve the lives of other women who use drugs drove motivation to participate in research, (3) preference for monetary compensation, which increased the likelihood of in research participation; and (4) women participated when research environments were supportive and destigmatized. Conclusion To recruit women who use drugs, researchers should collaborate with trusted community organizations, promote the benefits of research to other women, monetarily and fairly compensate participants, and foster supportive destigmatized environments.